Mapping the Landscape of Physics Education Research on Local Wisdom: A Bibliometric Study - Hanan Zaki Alhusni; Binar Kurnia Prahani; Titin Sunarti; Arfiati Ulfa Utami; Joana Paula Gerabella da Costa Moniz; Bauyrzhan Yedilbayev; Akmaral Shokanova; Sandygul Akhmetkaliyeva (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to map the research landscape of physics education that integrates local wisdom. It identifies key trends, author collaborations, and thematic clusters in publications, providing insights for future research and curriculum development. Method: A bibliometric analysis approach was employed, collecting articles from Google Scholar using the Publish or Perish software, with a focus on publications from 2018 to 2024. The PRISMA protocol was followed for systematic data screening, resulting in 150 relevant articles. The metadata was analyzed using VOSviewer to generate visualizations of keyword networks, author collaborations, and research clusters. Results: The analysis revealed that